Improving edge crystal identification in flood histograms using triangular shape crystals. (9th February 2018) - Peng, Peng; Liu, Chih-Chieh; Du, Junwei; Bai, Xiaowei; Cherry, Simon R
Abstract: This work presents a method to improve the separation of edge crystals in PET block detectors. As an alternative to square-shaped crystal arrays, we used an array of triangular-shaped crystals. This increases the distance between the crystal centres at the detector edges potentially improving the separation of edge crystals. To test this design, we have compared the flood histograms of two 4 × 4 scintillator arrays in both square and triangular configurations. The quality of the flood histogram was quantified using the fraction of events positioned in the correct crystal based on a 2D Gaussian fit of the segmented flood histograms. In the first study, the two crystal arrays were coupled with the SiPM directly using optical grease, and the flood histogram quality for the edge and corner crystals in the triangular-shaped array were much better than that for those crystals in the square-shaped array. The average light collection efficiency for the triangular-shaped array was 5.9% higher than that for the square-shaped array. The average energy resolution for the triangular and square shape array were 11.6% and 13.2% respectively. In the second study, two light guides with thickness 1 mm and 2 mm were used between the crystal arrays and the SiPM. The thicker lightguide degraded the light collection efficiency and energy resolution due to the light loss introduced by the light guide. However, in the 2 mm thick lightguide case, the flood histogram quality for the edge and corner crystals in the square-shaped array were improved due to better separation of those crystals in the flood histogram. Comparing the performance of the two crystal arrays with three different light guides, the triangular-shaped crystal array with no lightguide gave the best performance.